2013
DOI: 10.1088/0022-3727/46/40/404008
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the tribological behaviour of Y-TZP in tea and coffee under micro-abrasion conditions

Abstract: The micro-abrasion of YTZP, a candidate dental restorative material, was investigated in a range of caffeine containing solutions which included tea and coffee. Additions of sugar and milk were used to test the effects of viscosity and pH on the wear rate. The results indicated a significant increase in wear rate in the various solutions, with some correlation between wear rate and increases in viscosity and this was linked to enhance particle entrainment in the more viscous solutions. The generally lower wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Figure 5d also shows a higher magnification of 3 hour, 4N applied load wear scar where the entrainment of the abrasive particles have taken place. Particle entrainments can cause an increase of the wear rate as more particles become entrained further entrainment happens more quickly, resulting in higher wear rates [31]. However, the rate of entrainment can vary under different applied loads depending on the possibility of ridge formations [41].…”
Section: Sem Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5d also shows a higher magnification of 3 hour, 4N applied load wear scar where the entrainment of the abrasive particles have taken place. Particle entrainments can cause an increase of the wear rate as more particles become entrained further entrainment happens more quickly, resulting in higher wear rates [31]. However, the rate of entrainment can vary under different applied loads depending on the possibility of ridge formations [41].…”
Section: Sem Resultsmentioning
confidence: 99%
“…Also, softer particles degrade in such conditions which are not suitable for the current study. The hardness of alumina makes them an appropriate choice to create severe conditions and assess the longevity of the test materials [31]. The flatness of the alumina particles can also spread the load effectively at the interface [32].…”
Section: Test Slurrymentioning
confidence: 99%
“…The combination of the rotational speed and test length resulted in a total sliding distance of 359 m per test. Previous studies have shown that the average sliding distance per tooth each day is approximately 1 m. Thus, each test approximates 1 year of material use as a crown [14].…”
Section: Test Methodologymentioning
confidence: 99%
“…Previous works examined the effects of particle size and concentration [11][12][13]. For these tests, a concentration of 30 gl -1 of particles with the average size of 9 lm was used to maintain the consistency with the previous studies [3,6,14]. The abrasive particles were kept suspended using a mechanical stirrer during the testing, and the solution was replaced after a maximum of 1 h testing.…”
Section: Test Slurrymentioning
confidence: 99%
See 1 more Smart Citation